2018
DOI: 10.1111/jebm.12325
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice of physicians toward evidence‐based medicine: A systematic review

Abstract: Aim: To assess knowledge, attitude, and practice of graduate physicians toward evidence-based medicine (EBM) and the barriers to the implementation of EBM worldwide. Methods:Relevant databases were searched systematically with appropriate search terms up to September 2017. References of the articles detected by the search were screened for any new articles. Risk of bias was assessed by two independent reviewers. Data were extracted from the full-text articles based on the study summary measures and were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 49 publications
7
53
1
4
Order By: Relevance
“…Moreover, more than half of the members were completely unaware of the Cochrane Library (28). According to multiple studies, the low level of knowledge among dental students opposes strong attitudes and limits the clinical use of the EBD approach (27,28,(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, more than half of the members were completely unaware of the Cochrane Library (28). According to multiple studies, the low level of knowledge among dental students opposes strong attitudes and limits the clinical use of the EBD approach (27,28,(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…When looking at attitudes and practice toward evidence‐based medicine (EBM), Barzkar et al performed a systematic review demonstrating an overall positive attitude from physicians toward the idea of practicing EBM; however, they reported awareness and knowledge was poor due to similar barriers as those stated above . How, then, can providers overcome these barriers to realize their desire to practice EBM consistent with published CPGs?…”
Section: Discussionmentioning
confidence: 99%
“…7,8,[18][19][20] Barzkar et al summarized the knowledge, attitudes and practice (KAP) of physicians in a systematic review including 57 articles and reported that physicians generally have positive attitude toward EBM and most believe that its implementation improves patient care but found that their self-reported awareness and knowledge regarding EBM concepts to be generally poor. 10 Based on a literature review, no study in Nigeria has assessed the KAP of EBM among resident doctors who are responsible for the majority of clinical decision making in tertiary hospitals. This study therefore, assessed the self-rated EBM KAP and barriers among resident doctors in a selected teaching hospital in southern Nigeria.…”
Section: Udod Andmentioning
confidence: 99%
“…First, clinician's understanding of this care delivery strategy may be poor; for example, findings from studies suggested that a low proportion of clinicians understood the components of EBM in some settings 6,7 . Apart from knowledge, clinicians do also face other barriers in adopting the EBM concepts, the most consistently documented of which is the lack of time to search for, retrieve and study evidence each time a clinical question is raised 7‐12 . The time barrier and similar challenges are probably of higher relevance in resource‐constraint settings like Nigeria with a low doctor‐population ratio of 4 in 10 000, 13 and an average consultation time of 10 minutes or less 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation